Community Empowerment in Malaria Elimination in Mbatakapidu Village - Kody, Martha Meti; Noviana, Ineke; Rija, Tatu (PT FORMOSA CENDEKIA GLOBAL, 2025)
61.9% or 318 districts/cities were declared malaria-free and there are still 196 districts/cities that are targeted for elimination. The total number of malaria sufferers in Mbatakapidu village is 6 sufferers in 2020, 55 in 2021, 155 in 2022 and has decreased, namely in 2023 the number of sufferers is 56. The goal is to improve community knowledge and skills in the health sector by providing independent malaria prevention education that can be carried out by the community, developing independent community groups in the health sector by empowering malaria cadres and providing education to the community regarding the use of mosquito nets Results: There was an increase during the post-test, namely good 68% and sufficient 32%. The Mbatakapidu Village community became aware of malaria and procedures for modifying the environment and learned about the importance of maintaining cleanliness both in the environment and in the house.